2021
DOI: 10.1161/jaha.121.021965
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Based Differences in Bleeding Risk After Percutaneous Coronary Intervention and Implications for the Academic Research Consortium High Bleeding Risk Criteria

Abstract: Background Female sex was not included among the high bleeding risk (HBR) criteria by the Academic Research Consortium (ARC) as it remains unclear whether it constitutes an HBR condition after percutaneous coronary intervention. We investigated whether female sex associates with HBR and assessed the performance of ARC HBR criteria separately in women and men. Methods and Results Among all consecutive patients undergoing percutaneous coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…On the same issue, also personality traits and social roles traditionally ascribed to women could help explaining longer diagnosis and treatment delays in women [ 22 ]. Finally, women present also procedural technical aspects (such as an higher rate of radial artery spasm) that could leads to an increased risk of complications (access site bleeding and contrast induced nephropathy) and receive less frequently guideline-suggested treatments in comparison with men [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the same issue, also personality traits and social roles traditionally ascribed to women could help explaining longer diagnosis and treatment delays in women [ 22 ]. Finally, women present also procedural technical aspects (such as an higher rate of radial artery spasm) that could leads to an increased risk of complications (access site bleeding and contrast induced nephropathy) and receive less frequently guideline-suggested treatments in comparison with men [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ARC-HBR criteria were established to standardize the definition of HBR and promote consistency across trials evaluating this vulnerable subset of patients [ 31 ]. A number of studies have reported on the predictive value of the ARC-HBR definition in identifying patients at increased risk not only for bleeding but also for thrombotic events [ 18 , 32 34 ], as well as validated the clinical usefulness of the ARC-HBR criteria in relation to clinical presentation and sex [ 35 , 36 ]. Given that bleeding risk was a major reason for discontinuation of DAPT, we also assessed the effects of DAPT interruption ≤12 months compared with DAPT maintenance >12 months in a contemporary PCI population at high ischemic risk and HBR ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that women are less likely to receive acute reperfusion therapy [ 148 , 149 ] and optimal medical therapy (OMT) [ 148 ]. Finally, the female gender represents an independent risk factor for peri-procedural AMI and major bleedings after percutaneous coronary intervention, which is notably associated with increased mortality [ 58 , 150 ].…”
Section: Gender Differences In Cardiovascular Diseases: From Epidemio...mentioning
confidence: 99%
“…The diagnosis of MINOCA should be made following the Fourth Universal Definition of myocardial infarction (MI), requiring an AMI in the absence of obstructive CAD (no lesion ≥50%) [ 152 ]. MINOCA occurs in 5–6% of AMI [ 150 ]. A differential diagnosis from other cardiac and noncardiac disorders is essential [ 167 ].…”
Section: Gender Differences In Cardiovascular Diseases: From Epidemio...mentioning
confidence: 99%